Silicon nitride chemical vapor deposition from dichlorosilane and ammonia: theoretical study of surface structures and reaction mechanism - Bagatur'yants, Alexander A.; Novoselov, Konstantin P.; Safonov, Andrei A.; Vernon Cole, J.; Stoker, Matthew; Korkin, Anatoli A. (Surface science, 2001)
The structure of a Si 3N 4 film and the mechanism of Si 3N 4 film growth along the [0 0 0 1] crystal direction during chemical vapor deposition have been examined using ab initio MP2/6-31G** calculations. The silicon nitride (0 0 0 1) surface and deposited (chemisorbed) species on this surface were described using cluster models. It was found that the dangling bonds of chemically bound Si and N atoms on the bare surface are relaxed to form additional π bonds or SiN surface double bonds. Energies of reaction and activation energies were calculated and the process of Si 3N 4 film growth was analyzed. It was found that the removal of chemically bound hydrogen from the surface is the rate-controlling step of the deposition process.